Acehnese Language Learning Materials through Animated Videos to Enhance Literacy and Cultural Identity Among Elementary Students - Inas Ghina; Rahil Helmi; Wita Dwi Payana; Miftahul Husna (Universitas Pendidikan Ganesha, 2025)
The limited availability of engaging learning media and the lack of contextual teaching materials lead to low student interest and engagement in regional language learning. This study aims to develop animated video-based Acehnese language learning materials to improve literacy skills and strengthen the cultural identity of elementary school students. This study uses a research and development approach with the Four-D model. The research subjects involved elementary school students and language and education experts as validators. Data collection was conducted through interviews, validation questionnaires, practicality questionnaires, and learning outcome tests. The research instruments consisted of media, language, and culture validation sheets and test kits. Data were analyzed descriptively based on the validation results, user responses, and student learning outcomes. The results showed that the developed animated video-based Acehnese language learning materials were deemed valid, practical, and effective in supporting the learning process. These findings suggest that the integration of culture-based digital media can be an effective learning strategy in improving regional language literacy while strengthening students' cultural identity. The implications of this study emphasize the importance of utilizing innovative technology-based learning media to support regional language revitalization and encourage teachers to develop more contextual and engaging learning.